Community-Based Case–Control Study of Childhood Stroke Risk Associated With Congenital Heart Disease. Issue 2 (February 2015) - Fox, Christine K.; Sidney, Stephen; Fullerton, Heather J.
Abstract : Background and Purpose—: A better understanding of the stroke risk factors in children with congenital heart disease (CHD) could inform stroke prevention strategies. We analyzed pediatric stroke associated with CHD in a large community-based case–control study. Methods—: From 2.5 million children (aged <20 years) enrolled in a Northern California integrated healthcare plan, we identified children with ischemic and hemorrhagic strokes and randomly selected age- and facility-matched stroke-free controls (3 per case). We determined exposure to CHD (diagnosed before stroke) and used conditional logistic regression to analyze stroke risk factors. Results—: CHD was identified in 15 of 412 cases (4%) versus 7 of 1236 controls (0.6%). Cases of childhood stroke (occurring between ages 29 days to 20 years) with CHD had 19-fold (odds ratio, 19; 95% confidence interval 4.2–83) increased stroke risk compared to controls. History of CHD surgery was associated with >30-fold (odds ratio, 31; confidence interval 4–241) increased risk of stroke in children with CHD when compared with controls. After excluding perioperative strokes, the history of CHD surgery still increased the childhood stroke risk (odds ratio, 13; confidence interval 1.5–114). The majority of children with stroke and CHD were outpatients at the time of stroke, and almost half the cases who underwent cardiac surgery had their stroke >5 years after the most recent procedure. An estimated 7% of ischemic and 2% of hemorrhagic childhood strokes in the population were attributable to CHD. Conclusions—: CHD is an important childhood stroke risk factor. Children who undergo CHD surgery remain at elevated risk outside the perioperative period and would benefit from optimized long-term stroke prevention strategies. Abstract : Supplemental Digital Content is available in the text.